Business and industry in Nazi Germany - Nicosia, Francis R., 1944-; Huener, Jonathan (Studies in business history., 2004)
During the past decade, the role of Germany's economic elites under Hitler has once again moved into the limelight of historical research and public debate. This volume offers a brief but focused introduction to the role of Germany businesses and industries in the crimes of Hitler's Third Reich.